1987
DOI: 10.1101/gad.1.6.556
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli tryptophan repressor binds multiple sites within the aroH and trp operators.

Abstract: The Trp repressor of Escherichia coli coordinately regulates the expression of the trp, aroH, and trpR operons in response to the intracellular levels of L-tryptophan (Cohen and Jacob 1959;Brown 1968;Rose et al. 1973;Gunsalus and Yanofsky 1980). The trpR operon, located at 99.5 min, codes for the Trp aporepressor and is autoregulated (Morse and Yanofsky 1969;Gunsalus and Yanofsky 1980;Kelley and Yanofsky 1982;Bachman 1983;Gunsalus et al. 1986). The aroH operon, located at 37 min, encodes one of the three isozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
66
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 28 publications
12
66
0
Order By: Relevance
“…Consistent with these results, Bennett and Yanofsky (1978)have isolated constitutive mutations at positions + 4, + 5, and -6 within the trp operator half-sites that represent four of these eight most critical changes. The G : C base pairs in the natural operators implicated in binding by Kumamoto et al (1987) include the same G:C base pairs identified as important by our genetic method.…”
Section: Operator Determinants Of Bindingmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with these results, Bennett and Yanofsky (1978)have isolated constitutive mutations at positions + 4, + 5, and -6 within the trp operator half-sites that represent four of these eight most critical changes. The G : C base pairs in the natural operators implicated in binding by Kumamoto et al (1987) include the same G:C base pairs identified as important by our genetic method.…”
Section: Operator Determinants Of Bindingmentioning
confidence: 99%
“…Our results, taken together with the crystal structure of Trp repressor (Schevitz et al 1985) and data from chemical protection experiments that define the interaction of Trp repressor with naturally occurring operators (Kumamoto et al 1987), enable us to construct a model for the specificity determinants of the Trp repressor/operator interaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lisa Klig and Barry Hurlburt of my group, with Tom Graddis and Dale Oxender at the University of Michigan, and independently Janette Carey of Princeton, identified many additional features of the trp repressor (72,73). After leaving my lab, Robert Gunsalus contributed the interesting finding that there appear to be multiple repressor binding sites in the trp operon operator region (74). Catherine Lawson and Janette Carey provided conclusive structural evidence in support of this proposition (75).…”
Section: Investigating Repressionmentioning
confidence: 93%